2012
DOI: 10.1371/journal.pone.0029446
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Immunization Protects against Lethal, Extreme Drug Resistant-Acinetobacter baumannii Infection

Abstract: Extreme-drug-resistant (XDR) Acinetobacter baumannii is a rapidly emerging pathogen causing infections with unacceptably high mortality rates due to inadequate available treatment. New methods to prevent and treat such infections are a critical unmet medical need. To conduct a rational vaccine discovery program, OmpA was identified as the primary target of humoral immune response after intravenous infection by A. baumannii in mice. OmpA was >99% conserved at the amino acid level across clinical isolates harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
184
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(188 citation statements)
references
References 49 publications
(68 reference statements)
4
184
0
Order By: Relevance
“…That study, while promising, had the limitation of the undefined nature of the vaccine preparations. Another study evaluated OmpA as a target for vaccination against extreme drug-resistant A. baumannii infections (22), but only a single A. baumannii strain was evaluated, which limits the interpretation of those findings.…”
Section: Discussionmentioning
confidence: 99%
“…That study, while promising, had the limitation of the undefined nature of the vaccine preparations. Another study evaluated OmpA as a target for vaccination against extreme drug-resistant A. baumannii infections (22), but only a single A. baumannii strain was evaluated, which limits the interpretation of those findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated various vaccine candidates against A. baumannii infection [31]. Recently, AbOmpA has been considered as a potent vaccine candidate for protection against A.baumannii infections in diabetic mice models [32]. The results of our study showed that outer membrane protein A is widespread among the pathogenic members of Enterobacteriaceae and non-Enterobacteriaceae families such as A. baumannii.…”
Section: Discussionmentioning
confidence: 64%
“…baumannii challenge; use of antibodies against OmpA also elicited similar protective efect on diabetic mice with lethal A. baumannii infection [168]. Interestingly, dosage of A. baumannii rOmpA vaccine correlates with various B cell epitopes and immunodominant T cell epitopes, emphasizing dosage needs to be taken into account for vaccine development [169].…”
Section: Targeting Outer Membrane Protein a (Ompa)mentioning
confidence: 99%
“…OmpA can bind with host cell directly, internalize within mitochondria and nuclei compartments of host cell, and induce host cell death [165,166]. Moreover, OmpA is highly conserved within six clinical isolates (99% protein sequence identity) and 14 other NCBI GenBank deposited sequences from diferent isolates of A. baumannii (89% protein sequence identity), while OmpA shows no homology to human proteins [168].…”
Section: Targeting Outer Membrane Protein a (Ompa)mentioning
confidence: 99%